Supramolecular polyners - Ciferri, Alberto (Taylor and Francis, 2005)
The book highlights developments in the synthesis of complex structures, chemical design principles, and theoretical models of growth processes resulting in an increasingly accurate prediction of stability, degree of polymerization, and shape of various assemblies. It focuses on the rich variety of properties, functions, and applications of self-assembling supramolecular polymers. Supramolecular Polymers, Second Edition ties together potential applications such as those of nanostructures with dynamic-combinatorial-adaptive self-healing features, opto-electronic devices, supramolecular amphiphiles, hydrogels, organic/inorganic nanocomposites, molecular biosensors, molecular imprinting, molecular engines, templates for superlattices with prescribed symmetry. Several chapters of the first edition have been updated or rewritten, and an equal number of new chapters have been added. More than 500 drawings, photographs, micrographs, equations, and tables enhance and reinforce essential concepts presented in the book.